DETERMINANTS OF PROFITABILITY OF CONVENTIONAL COMMERCIAL BANKS IN INDONESIA FOR THE 2018–2020 PERIOD - Anang Aryokho; Muji Gunarto; Isfarudi Isfarudi (Bajang Institute, 2023)
This study aims to examine the effect of CAR, NPL, BOPO and LDR on ROA of Conventional Commercial Banks listed at OJK in 2018-2020. The population and sample in this study were 77 conventional commercial banks with a sample of 231 observational data. The type of data used is secondary data on banking annual financial reports published at OJK for 2018-2019. The sampling technique used purposive sampling technique with panel data regression analysis method with Eviews 10 analysis tool. The results showed that CAR had a positive and significant effect on ROA, NPL and BOPO had a negative and significant effect on ROA, and LDR had a positive but not significant effect on ROA. significant to ROA